(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Any disease pertaining to skin causes adverse impact on psychological and social well-being results in depression, social isolation, loneliness and reduce quality of life. WHO has classified skin diseases a psycho-cutaneous disease which emphasizes the relation between skin and psyche. Hence skin ailments are given high priority by the patients. Skin diseases are commonly observed thanks to altered lifestyle including improper and altered food habits, mental stress, improper sleeping habits and poor hygiene. In Ayurveda, the majority the skin diseases are incorporated under Kustharoga and are classified as Mahakustha (major skin disorders) and Kshudra kustha (minor skin disorders). Kitibha kustha is explained under Kshudra kustha in Ayurvedic Samhitas. The signs and symptoms of Kitibha kustha are same as that of psoriasis explained in modern science. Aim: The aim was to gauge the importance of Vamana karma (bio-purificatory measures) in Kustha. Materials and Methods: A male patient aged 18 years presented with the signs and symptoms of slightly raised well-defined brownish patches over upper middle back, behind both ears and around both alar nasal sulcus associated with itching diagnosed it as Kitibha kustha and was treated with Vamana karma (emesis) followed by prior Deepan karma and Bahya & Abhyantar snehan (internal & external oiling) followed by Swedan (fomentation). Results: At the conclusion of Vaman, Pittantik vamana was achieved. Patient had significant relief from Kandu (itching), scaling and reduction of erythema after the procedure. Photographic changes were kept for comparison. Conclusion: This present case study revealed the importance of Vamana karma in Kitibha kustha (Psoriasis).